1985
DOI: 10.1227/00006123-198506000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Rathke's Cleft Cysts Located Entirely in the Suprasellar Region: Review of Diagnosis, Management, and Pathogenesis

Abstract: Three cases of an entirely suprasellar symptomatic Rathke's cleft cyst, two of which were associated with normal sella turcicas, are reported. In all cases, the cysts caused compression of the optic chiasm, and two produced hypothalamic dysfunction. The diagnosis of these entirely suprasellar masses was enhanced by metrizamide cisternography. Two cases were treated by frontal craniotomy and one was treated transsphenoidally, with good results in all cases. The radiology, pathology, and surgical treatment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 0 publications
2
29
1
Order By: Relevance
“…The vast majority of lesions are intrasellar or intra-and suprasellar, with reports of purely suprasellar lesions occurring in a minority of patients. 6,110 The normal pituitary gland may be displaced in any direction by an RCC, including circumferentially if the cyst arises in and remains encased within the gland. 10,86 In the majority of cases, administration of Gd contrast material demonstrates little or no enhancement of the cyst wall or contents on MR imaging.…”
Section: Typical Imaging Features Of Rccsmentioning
confidence: 99%
“…The vast majority of lesions are intrasellar or intra-and suprasellar, with reports of purely suprasellar lesions occurring in a minority of patients. 6,110 The normal pituitary gland may be displaced in any direction by an RCC, including circumferentially if the cyst arises in and remains encased within the gland. 10,86 In the majority of cases, administration of Gd contrast material demonstrates little or no enhancement of the cyst wall or contents on MR imaging.…”
Section: Typical Imaging Features Of Rccsmentioning
confidence: 99%
“…44,51 The pars tuberalis lies above the diaphragm, and the Rathke's pouch remnants in this location can give rise to an entirely suprasellar RCC. 4 Entirely suprasellar RCCs with a normal sella turcica are relatively rare (incidence 0%-20%). 8,12,13,15,20,24,25,31,36,39 Suprasellar, intrasuprasellar, and intrasellar RCCs are distinct entities with respect to their clinical presentation, resectability, postoperative recurrence, and outcomes.…”
mentioning
confidence: 99%
“…However, a few cells may migrate outside the sellar region. 2,10 Under such circumstances, the failure of these ectopic cells to regress during development may lead to the formation of an ectopic RCC. Our pathological examination showed that the cyst was lined partially by columnar epithelium and partially by stratified squamous epithelium, which overlapped histological features with the craniopharyngioma.…”
Section: Discussionmentioning
confidence: 99%